PENGUJIAN PERATURAN PERUNDANG-UNDANGAN DI BAWAH UNDANG-UNDANG OLEH MAHKAMAH AGUNG - Sudarsono Sudarsono (universitas islam darul ulum lamongan, 2017)
In realizing unity in the legislation system in Indonesia, it is known that there is a Judicial Review conducted by the Constitutional Court and the Supreme Court. Article 9 of Law Number 12 Year 2011 concerning the establishment of laws and regulations states that the Constitutional Court has the authority to examine the legality of a law with the test stone of the 1945 Constitution of the State of the Republic of Indonesia, while the Supreme Court has the authority to examine the legality of a legislation under the law with a test stone legislation. The Supreme Court in exercising its authority has issued the Supreme Court Regulation No. 1 of 2011 on the Right to Material Test. In its development, the Supreme Court Regulation Number 1 Year 2011 needs to be refined, whether related to the definition of